2006
DOI: 10.1080/00140130600708206
|View full text |Cite
|
Sign up to set email alerts
|

Bicycle messengers: energy expenditure and exposure to air pollution

Abstract: The purpose of the study was to determine the level of energy expenditure and exposure to air pollution for bicycle messengers. Relationships between heart rate (HR) and oxygen uptake, and between HR and pulmonary ventilation (VE) for each participant were established in laboratory tests. Air pollution and HR were measured during one working day. The total oxygen uptake was then described as the total energy expenditure in Joule (J) and in multiples of the energy expenditure at rest (MET). The mean energy expe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
28
0
2

Year Published

2010
2010
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(33 citation statements)
references
References 12 publications
3
28
0
2
Order By: Relevance
“…The estimated coefficients in Table 3 are in line with the literature, which suggests central values of 0.016-0.023 for bicyclist lṅ~ slope coefficients , heterogeneous to individuals (1,18,20,21). Mermier et al (8) report slopes ranging from 0.016 to 0.029 for 15 healthy men who performed maximum exercise tests on ergometers.…”
Section: Ventilation and Heart Ratesupporting
confidence: 77%
“…The estimated coefficients in Table 3 are in line with the literature, which suggests central values of 0.016-0.023 for bicyclist lṅ~ slope coefficients , heterogeneous to individuals (1,18,20,21). Mermier et al (8) report slopes ranging from 0.016 to 0.029 for 15 healthy men who performed maximum exercise tests on ergometers.…”
Section: Ventilation and Heart Ratesupporting
confidence: 77%
“…Minute ventilation has been reported as 22-59 L/min for bicyclists: two to five times higher than for travelers in automobiles or at rest. Bernmark et al (2006) found V E peaks for bicycle messengers of up to 97 L/min. The ranges of minute ventilations in Table 2 are related to the different average travel speeds and heart rates among the studies (included in Table 2), as well as potentially other experimental differences such as terrain, bicycle weight and condition, weather, and subject fitness.…”
Section: Respirationmentioning
confidence: 99%
“…Methodologies are categorized as 'on-road' (direct on-road measurement of respiration using masks), 'lab' (laboratory ergometer-based respiration measurements), and 'estimated' (on-road measurement of heart rate and estimation of respiration using laboratory ergometer-based heart rate/ventilation relationships). MET of energy expenditure, with power output of roughly 50-150 W, depending on the speed (Bernmark et al, 2006;De Geus, de Smet, Nijs, & Meeusen, 2007;Whitt, 1971). MET values have been employed to estimate bicyclists' respiration for pollution dose assessments using both reference MET values and MET values estimated from accelerometer measurements; average accelerometerbased MET for bicycling was estimated at 6.58 with a corresponding ventilation rate of 41 L/min (De Nazelle et al, 2012).…”
Section: Respirationmentioning
confidence: 99%
“…A number of studies have looked at how cycling affects exposure to air pollution (Bernmark, Wiktorin, Svartengren, Lewné, & Å berg, 2006;Briggs, de Hoogh, Morris, & Gulliver, 2008;Chertok, Voukelatos, Sheppeard, & Rissel, 2004;de Nazelle et al, 2012;Gulliver & Briggs, 2004;Int Panis et al, 2010;Rank, Folke, & Homann Jespersen, 2001;Zuurbier et al, 2010). These studies estimate exposure to PM 2.5 while cycling to be about double the background pollution, and about 20% lower than while driving, although local circumstances are influential and ratios can vary considerably for different pollutants (Karanasiou et al, 2014).…”
Section: Exposure To Air Pollutionmentioning
confidence: 99%